(untitled) (Argos, 2025)
In this paper the conception of Cicero’s language in its rhetorical grammatical relationship is investigated. It is tackled by talking as starting point the stoical conceptions regarding the language, so as to mark the distancing of the Latin rhetoric and the constitution of an esthetics of the word with persuasion in mind. In keeping with this perspective, we continue in the study of the relationship between dialectic and rhetoric and the consequent definition of eloquence, in the conception of oratory as an artistic production and device which ends up in the hearer.